ORGANIZATION OF FIELD TRAINING FOR GEOGRAPHY STUDENTS IN THE FERGANA VALLEY - Odiljon Tobirov,; Xidoyatkhon Abdinazarova,; Azamjon Jobborov,; Azamat Khoshimov, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  Field  training is a fundamental component  of geography  education, enabling students to integrate theoretical knowledge with real-world observation and analysis.  This  article  examines  the  organization,  significance,  and  methodological foundations of field training for geography students in the Fergana Valley, a region characterized by diverse natural landscapes, complex socio-economic conditions, and environmental  challenges.  The  study  highlights  the  educational  value  of  hands-on fieldwork  in  developing  students’  practical  skills  in  geographical  data  collection, environmental  assessment,  and  spatial  analysis.  Particular  attention  is  given  to logistical  planning,  site  selection,  safety  considerations,  and  the  use  of  modern technologies  such  as  Geographic  Information  Systems  (GIS)  and  remote  sensing during  field  activities.  The  results  demonstrate  that  well-organized  field  training enhances students’ critical thinking, professional competencies, and understanding of local  environmental  and  cultural  contexts.  The  article  concludes  that  the  Fergana Valley provides an effective and versatile field laboratory for geography education and offers  recommendations  for  improving  future  field  training  programs  through interdisciplinary approaches and technological integration.